2018
DOI: 10.4172/2165-7890.1000223
|View full text |Cite
|
Sign up to set email alerts
|

National Prevalence and Correlates of Autism: A Lebanese Cross-Sectional Study

Abstract: Background: There is a lack of data regarding autism prevalence and factors associated with it in Arab Countries, especially in Lebanon. A study conducted in Beirut and Mount Lebanon governorates estimated the prevalence of Autism Spectrum Disorder (ASD) at 1.53% of children 16-48 months attending nurseries. This study aims at obtaining a total national ASD estimate and find factors associated with the disorder. Methods: The methodology used to collect data at a national level consisted of administering the Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 39 publications
1
1
0
Order By: Relevance
“…In fact, a study conducted on a large cohort of Swedish children showed that the heritability of the disorder is approximately 50% and the risk of ASD increases 10-fold if a sibling has the disease and 2-fold if a cousin is diagnosed with ASD [ 26 ]. However, this result was concordant with the finding of two Lebanese studies showing that familial history of mental illness and ASD are significantly associated with ASD onset in children [ 23 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…In fact, a study conducted on a large cohort of Swedish children showed that the heritability of the disorder is approximately 50% and the risk of ASD increases 10-fold if a sibling has the disease and 2-fold if a cousin is diagnosed with ASD [ 26 ]. However, this result was concordant with the finding of two Lebanese studies showing that familial history of mental illness and ASD are significantly associated with ASD onset in children [ 23 , 27 ].…”
Section: Discussionsupporting
confidence: 91%
“…This increase in prevalence has garnered attention worldwide. A study from Lebanon in 2018 estimated ASD prevalence in children attending nurseries between 16-48 months of age at 1.49 % (1 in 67) [6,7].…”
Section: Introductionmentioning
confidence: 99%